2017
DOI: 10.1039/c7ra02742g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of epitaxial crystallization on the mechanical properties of a high density polyethylene/reduced graphene oxide nanocomposite injection bar

Abstract: High density polyethylene (HDPE)/reduced graphene oxide (RGO) nanocomposite bars were prepared by injection molding and the effects of RGO on the HDPE matrix were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Therefore, on the basis of the DSC and WAXD results, the crystalline degree of PA66 slightly reduces with the increase of RGO in the PA66/RGO nanocomposites. The result of the crystalline degree is consistent with the result of the PE/RGO nanocomposites [42]. It may be due to the fact that RGO hinders the motion of polymer chains.…”
Section: Resultssupporting
confidence: 80%
“…Therefore, on the basis of the DSC and WAXD results, the crystalline degree of PA66 slightly reduces with the increase of RGO in the PA66/RGO nanocomposites. The result of the crystalline degree is consistent with the result of the PE/RGO nanocomposites [42]. It may be due to the fact that RGO hinders the motion of polymer chains.…”
Section: Resultssupporting
confidence: 80%
“…Crystalline polymers are widely used in automobile manufacturing, electronic devices, and building fields because of their better physical properties in comparison with amorphous polymers. [1][2][3] However, the present crystalline polymers are mainly based on general and engineering polymers, including polyvinyl chloride, 4 polyethylene, 5 polybutylene, 6 vinyl ester, 7 and so on. The mechanical strength, thermal stability, and antioxidation were still limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the PE chains can be absorbed and then epitaxially crystallized on RGO surfaces. In the injection moulding process of HDPE/RGO nanocomposites, it is reasonable that the flow field can also drive the preferred orientation of both HDPE chains and RGO nanosheets [30]. However, in the subsequent cooling course, the situation becomes different from that of pure polymers, for the release of the oriented large RGO nanosheets is rather hard to achieve.…”
Section: Resultsmentioning
confidence: 99%
“…So, when the content of RGO is quite small, the less but highly oriented RGO can also lead to the gently preferred orientation. Recently, we also reported that the introduction of RGO can enhance the mechanical properties of the injection bars of HDPE/RGO nanocomposites [30]. Here, by further investigating the microstructures via microbeam SAXS, despite the presence of weak difference in the enhancing effect at varied positions, especially for the cases of large RGO contents, we have demonstrated that the coupling between the flow-induced orientation and the RGO-depressed release of oriented chains by absorption and then epitaxial crystallization imposes an approximately uniform intensifying effect on the crystallization and orientation of HDPE in the flow direction, which results in the enhancement of the mechanical performance of injection bars of HDPE/RGO nanocomposites.…”
Section: Resultsmentioning
confidence: 99%